La metodologia Sei Sigma nei servizi - Ciappei, Cristiano (Firenze University Press, 2006)
This book explains how the methodological approach of the Six Sigma can be used to provide an effective solution to one of the most widespread problems faced by Small and Medium Enterprises: the frequent undercapitalisation linked to short-term investments often funded by bank loans. The Six Sigma method enables the problem to be tackled by studying, in an analytical and statistical manner, both the payments that the enterprises are to receive and the possible conditions of the funding, proposing solutions to optimise these processes and improve the financial performance of the SMEs. Hence the book is offered as both a methodological analysis and as an operative tool for the sphere of enterprise.